Peran Hormon Glukagon dalam Regulasi Metabolisme Energi dan Respon Stres pada Sapi Perah Periparturient: Literatur Review - Maulidina, Fauziah; Maulana, Irpan; Putria, Devita Rahma; Tuzzahra, Maulida Andini; Nurrofingah, Ulfa; Nafisah, Ainun (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The periparturient period of dairy cows is a transitional phase starting from three weeks before to three weeks after parturition with physiological changes characterized by increased energy needs for lactation and decreased feed consumption, resulting in a negative energy balance (NEB) and metabolic stress. The periparturient glucagon hormone plays an important role in maintaining the balance of energy metabolism through the activation of glycogenolysis and gluconeogenesis in the liver to maintain blood glucose levels, as well as encouraging lipolysis of adipose tissue that produces non-esterified fatty acids (NEFA) as an alternative energy source. Glucagon plays a role in maintaining the balance of metabolic adaptation to reduce disorders, such as ketosis, fatty liver, and decreased early lactation. The main objective is to analyze the role of the glucagon hormone in regulating energy metabolism and stress responses that interact with other hormones and nutritional factors that influence the physiology and metabolism of periparturient dairy cows. The discussion covers three main aspects, namely (1) the physiological mechanism of glucagon in energy metabolism, (2) the interaction of glucagon with other hormones such as insulin, GH, IGF-1, and cortisol, and (3) the effect of medium-chain fatty acids (MCFA) supplementation and rumen-protected glutamate on the activity and stability of glucagon secretion as a stress response in periparturient dairy cows. The writing method uses a literature review approach based on the analysis of the latest scientific journals relevant to the energy metabolism of dairy cows. The results of the study indicate that glucagon is the main regulator in the integration of endocrine and metabolic responses, works synergistically with other hormones and is influenced by nutritional status to maintain homeostasis, and reduce physiological stress. In conclusion, optimizing hormonal balance and nutritional management is very important to support metabolic efficiency, dairy cow productivity, and reduce stress during the periparturient period